Analisis Determinan Harga Saham Syariah pada PT. Indofood CBP Sukses Makmur Periode 2015-2019 - Khalik Pratama (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This article aims to analyze the influence of Earnings Per Share and Net Profit Margin on islamic stock prices in PT. Indofood CBP Sukses Makmur period 2015-2019. The issue is focused on discussing the impact of Earnings Per Share and Net Profit Margin on islamic stock prices. To approach this problem is used reference to signal theory. The data used is quarterly from March 2015 to December 2019. Research data was obtained from official sources, namely the Indonesia Stock Exchange (IDX) and the Jakarta Islamic Index (JII). The data analysis technique used was multiple linear regression. This review concluded that Earnings Per Share has a negative and significant influence on islamic stock prices, while Net Profit Margin has a positive and significant influence on islamic stock prices.